Heat‐Treated Adzuki Bean Protein Hydrolysates Reduce Obesity in Mice Fed a High‐Fat Diet via Remodeling Gut Microbiota and Improving Metabolic Function. Issue 8 (23rd February 2022) - Zhao, Qingyu; Fu, Yongxia; Zhang, Fan; Wang, Chao; Yang, Xuehao; Bai, Shuqun; Xue, Yong; Shen, Qun
Abstract : Scope: Heat‐treated adzuki bean protein hydrolysates (APH) reduce cholesterol in vitro. However, it is unclear if APH have anti‐obesity effects in vivo and, if so, the relationship between the effects and the improvement of gut microbiota composition and metabolic function. Methods and Results: Four groups of mice are fed either a normal control diet (NCD) or a high‐fat diet (HFD) with or without APH for 12 weeks. In HFD‐fed mice, APH supplementation significantly alleviate fat accumulation, dyslipidemia, insulin resistance, hepatic steatosis, and inflammation. In addition, APH supplementation regulate gut microbiota composition, reduce the abundance of harmful bacteria (Clostridium_sensu_stricto_1, Romboutsia, Blautia, Mucispirillum, Bilophila, and Peptococcus ), enrich Lactobacillus and SCFA‐producing bacteria ( Lactobacillaceae, Eisenbergiella, Alistipes, Parabacteroides, Tannerellaceae, Eubacterium_nodatum_group, Acetatifactor, Rikenellaceae, and Odoribacter ), and increase fecal SCFAs concentration. Importantly, APH supplementation significantly regulate the levels of serum metabolites, especially Lactobacillus ‐derived metabolites and tryptophan derivatives, which help to alleviate obesity and its complications. Conclusion: APH improve gut microbiota composition and metabolic function in mice and may help to prevent and treat obesity and related complications. Abstract : Heat‐treated adzuki bean protein hydrolysates (APH) alleviate obesity, dyslipidemia, insulin resistance, hepatic steatosis, and inflammation in HFD‐fed mice. Importantly, APH significantly modulate gut microbiota composition, increase fecal SCFAs concentration, and regulate the levels of serum metabolites, especially Lactobacillus ‐derived metabolites and tryptophan derivatives. Improvement in intestinal homeostasis and metabolic function may help to prevent and treat obesity.